Academic Help-Seeking and EFL Anxiety: A Correlational Study - Sari, Nur Laily Lupita; Saroh , Yam (JET ADI BUANA, 2025)
This study investigates the correlation between academic help-seeking behavior and foreign language anxiety (FLA) among Indonesian EFL learners enrolled in Foreign Language for Specific Purposes (FLSP) classes. Using a quantitative correlational design, data were collected from 90 undergraduate students across four faculties through two validated instruments: the Foreign Language Classroom Anxiety Scale (FLCAS) and the Academic Help-Seeking Scale. Pearson’s correlation revealed a significant negative relationship between academic help-seeking and FLA (r = –0.445, p < 0.05), indicating learners who actively seek academic assistance experience lower levels of anxiety, particularly regarding fear of negative evaluation—the most dominant FLA dimension. These findings highlight academic help-seeking as a self-regulated learning strategy that mitigates affective barriers and enhances emotional resilience in language learning. Nonetheless, the study’s cross-sectional design and limited sample size restrict generalizability. Future longitudinal and mixed-method studies are recommended to confirm causality and extend applicability across diverse educational context. Pedagogically, fostering supportive and collaborative classroom environments may encourage adaptive help-seeking and reduce anxiety, promoting greater learner autonomy and success in foreign language acquisition.